A study on the profile of ketum preparation using colour test and GCMS - Rosli, Wan Nur Qasrina Wan (2022)
Mitragyna speciosa, or known as ketum in Malaysia, is always misused as herbal drug of abuse. Typically, ketum is sold as their raw leaves, drinks or campsules in the street as well as incense online and also available at markets in more rural areas in Southeast Asia as traditional medicine, especially in Malaysia and Thailand. Ketum is very popular among men workers in Malaysia and Thailand. Many decades ago, ketum leaves have been used by natives due to its opium-like effect and cocaine-like stimulant ability to increase energy and combat fatigue. Mitragynine, an alkaloid from ketum leaves is responsible for these mentioned effects and this makes ketum drinks to become the emerging drug of abuse. However, it is unknown at all whether or not other ingredients were added in the ketum drinks available in the market.This present study was done to determine active compounds in the ketum drinks mixtures and to study the recent trend of ketum “cocktails”. In this study, all ketum drinks were obtained in the form of drinks. Presumptive colour test on ketum samples was successfully conducted using Van Urk reagent and 70 samples gave pink colour change, 4 samples gave dark pink colour change and one showed negative screening results. The preparation of ketum drink standard was successfully done by boiling 10 ketum leaves in a beaker on a hotplate. Besides, the extraction process of mitragynine from all 75 samples were successfully performed using liquid-liquid extraction method. Afterwards, the chloroform extracts were subjected to gas chromatographymass spectrometry (GC-MS) analysis. The resulting chromatograms and possible fragmentation pathways detected by GC-MS were discussed extensively. Out of 75 samples, only one sample did not exhibit mitragynine peak and majority showed simple chromatograms with only several peaks present in the chromatogram which include caffeine (RT=5.137) and mitragynine (RT=18.839). Sample 49 showed the most complex chromatograms with the presence of a MDMA peak. The trend of ketum drink mixtures in Malaysia was also studied. The findings showed that most of the ketum preparation were merely ketum drinks, without addition of any adulterants. A few samples were, however, in the form of cocktails, and these can cause serious health effects. It is therefore important that the monitoring of the streect drugs are conducted, perhaps via a more frequent drung profiling study to obtain information which could be useful for forensic intelligence as decision making for the respective authorities.